The European Commission's Approach to Long-term Contracts: an Economist's View. (17th August 2014) - Spector, David
Abstract: In recent decisions, the Commission has taken a hard stance vis-à-vis dominant firms using long-term contracts which, it contended, deterred rivals from effectively competing on relevant markets. Yet long-term contracts may have procompetitive effects pleading in favour of a fine-tuned enforcement.